Changes in peripheral nervous system at participants of accident consequences elimination in Chernobyl APP and population of the Tomsk northern industrial center - Ya. V. Porovsky; V. I. Zhankova; A. I. Ryzhov; Ye. V. Kalyanov; F. F. Tetenev (Бюллетень сибирской медицины, 2004)
A clinical, electroneuromyographic (ENMG) and pathomorphological investigation of 19 eliminators of accident consequences (EAC) in Chernobyl APP in 1986 and 27 Tomsk region inhabitants living in the accident area that has taken place at radiochemical plant of Siberian Chemical Complex in 1993 has been made with the aim of the influence study of low ionizing radiation levels on the peripheral nervous system. Symptoms of sensory polyneuropathy prevailed in both groups clinically. Mixed affection type has been found at EAC by ENGM method, affection of myelinic nerve fibre membrane has been found at people living in accident trace area. Morphofunctional changes in skin allow considering the role of immune system in mechanisms of neuroglial and neuronal damages, distant by time.